Microglial 'fat shaming' in development and disease. (December 2021) - Zareba, Joanna; Peri, Francesca
Abstract: Neuronal-immune interactions are known to play crucial roles in brain development and homoeostasis. Of great relevance in this context are microglia, brain macrophages that phagocytose neurons that die during development, and many neurological disorders. Single-cell RNA sequencing methods have significantly advanced our understanding of microglial heterogeneity and transcriptional response to environmental changes. Here, we review recent work showing how microglia adopt a similar molecular signature during development and disease characterised by the expression of genes linked to phagocytosis and lipid uptake and metabolism. These studies show that in many neurodegenerative conditions, microglia accumulate cholesterols and lipid-rich debris, pointing to lipid processing and transport as promising targets for developing new therapeutical treatments against neurodegenerative disorders.